Symmetry and non-lie reduction of the nonlinear Schrödinger equation - Fushchich, V. I.; Chopik, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The nonlinear Schrödinger-type equations invariant with respect to the extended Galilean group are described. We study the conditional symmetry of such equations, realize the reduction procedure, and construct the classes of exact solutions.